ANALISIS PEMBANGUNAN BANDARA KEDIRI TERHADAP PERKEMBANGAN SOSIAL EKONOMI DI DAERAH KECAMATAN GROGOL KOTA KEDIRI - Fitrias, Liffi Yanu; Faisol; Nurdiwaty, Diah (Prosiding Seminar Nasional Manajemen, Ekonomi dan Akuntansi, 2024)
This research aims to see the impact of socio-economic development around Dhoho Kediri airport. The people of GrogolDistricts are the population in this study, especially in Grigil Village Bedrek Hamlet. The object of this research is qualitativedescriptive research, a data analysis technique. In this research, 1 data source is used, namely primary data. Data collectionprocedures in this research used observation, interviews, documentation, and research sites using case studies. The resultsin this research use 2 impacts of the construction of the Dhoho Kediri airport: (1) the impact of airport construction on socioeconomic development seen from the social aspect and (2) the impact of airport construction on socio-economic development seen from the economic aspect.